Legend of Moulin Huet - Freeth, Lizzie A. (Salt Lake City, UT : Project Gutenberg, 2004)
"Legend of Moulin Huet" by Lizzie A. Freeth is a historical novel set in the mid-17th century during the tumultuous times of Cromwell's rule in England. Taking place primarily on the picturesque island of Guernsey, the story focuses on themes of love, jealousy, and revenge, encapsulated in the tale of the miller Pierre Moullin and the tragic consequences of his hatred towards his daughter's suitor. The narrative centers around Pierre Moullin, a grim and unyielding miller, who despises the Royalist soldier Charlie Heyward, due to his daughter Marguerite's love for him. In a fit of rage, Pierre conspires with Jacques Gaultier, a man deeply infatuated with Marguerite, plotting to eliminate Charlie. This jealousy culminates in a dramatic incident involving the mill wheel that nearly claims Charlie's life, impacting all characters involved and igniting a series of tragic events. The interplay of familial loyalty, betrayal, and the bitter conflict of loyalties during this period is woven through the relationships and struggles faced by the characters, ultimately leading to a resolution that allows love to triumph amidst the remnants of tragedy. (This is an automatically generated summary.)
Release date is 2004-11-22
E-text prepared by Steven Gibbs and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Channel Islands -- History -- Puritan Revolution, 1642-1660 -- Fiction